2018
DOI: 10.1080/13607863.2017.1423034
|View full text |Cite
|
Sign up to set email alerts
|

Perceived discrimination and mental health among older African Americans: the role of psychological well-being

Abstract: The prevalence of institutional lifetime discrimination for older African American men is consistent with previous research. Inconsistency with past research indicated that only everyday discrimination is statistically associated with depressive symptoms. Considering the buffering role of psychological well-being served for mental health problems, practitioners need to emphasize these factors when providing services to older African Americans. Equally important, they must address racial discrimination in menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…[28] In another study, higher levels of everyday discrimination (measured continuously) were associated with worse mental health as reported on the SF36 Mental Health Component Summary. [34] Five studies found significant associations between perceived institutional racism and mental health outcomes. A study that assessed the relationship between perceived institutional discrimination and healthrelated quality of life found that increased discrimination was associated with poorer mental health, one component of the quality of life scale.…”
Section: Associations Between Racism and Mental Healthmentioning
confidence: 99%
“…[28] In another study, higher levels of everyday discrimination (measured continuously) were associated with worse mental health as reported on the SF36 Mental Health Component Summary. [34] Five studies found significant associations between perceived institutional racism and mental health outcomes. A study that assessed the relationship between perceived institutional discrimination and healthrelated quality of life found that increased discrimination was associated with poorer mental health, one component of the quality of life scale.…”
Section: Associations Between Racism and Mental Healthmentioning
confidence: 99%
“…Everyday racism-"the various types and expression of racism experienced by ethnic groups in everyday contact with members of the more powerful (White) group" (Essed, 1990, p. 31)-predicts psychological distress (Harrell, 2000;Utsey et al, 2002;Williams et al, 2003), including higher rates of depressive symptomatology (Hammond, 2012;Powell et al, 2016;Utsey & Payne, 2000). Extant literature provides well-documented evidence of the association between everyday racism and negative psychological outcomes among Black men (Carter, 2007;Franklin, 1999;Franklin et al, 2006;Pierce, 1995;Sue, 2008;Yoon et al, 2019). Importantly, racism co-occurs with other life stressors including the stresses of work, partnership, finances, health, and home (Chung et al, 2014;Pieterse & Carter, 2007).…”
Section: Everyday Racism and General Life Stressmentioning
confidence: 99%
“…Although sparse, studies of Black adults have found similar relations. For example, among older Black women, a sense of purpose was inversely associated with mental health challenges (Yoon et al, 2019). Among African American women EWB has also been shown to be inversely related to depression (Lamis et al, 2014) and positively related to the use of active and effective coping strategies (Stevens-Watkins et al, 2014).…”
Section: Existential Well-being Spirituality and Pessimismmentioning
confidence: 99%
“…However, despite these additional stressors, evidence is emerging that some individuals can experience good health into older age. For example, a study of perceived discrimination and psychological well-being in African American older adults (N = 397; Age range = 65-89) found that the characteristic of 'self-acceptance', an awareness and acceptance of personal strengths and weaknesses, was shown to buffer the negative effect of discrimination on depressive symptomology, an indicator of psychological well-being (Yoon, Coburn, & Spence, 2019). Another study (Klokgieters, van Tilburg, Deeg, & Huisman, 2018a) examined the potential buffering effect of various religious activities against the negative impact of disadvantage (e.g., no/low resources) in older Turkish and Moroccan immigrants (N = 455; Age range = 55-66 years).…”
Section: Successful Aging In Racial and Ethnic Minoritiesmentioning
confidence: 99%